Intelligentsia and government authorities in modern Russia - O.V. Zolotarev (Ученые записки Казанского университета: Серия Гуманитарные науки)
The phenomenon of modern intelligentsia in Russia has been discussed in the paper. The roles played by intelligentsia in the sociopolitical situation during the late 20th – early 21 centuries have been considered. The essence of Russian intelligentsia and its current state have been revealed. Based on the data from the study of open-access published sources, common and peculiar features, achievements and problems of the modern Russian intellectual elite have been shown. The paper analyzes the independence of intelligentsia and today's political process in Russia. Special attention has been paid to the interrelations of the government and intelligentsia in modern Russia. The transformations in the perception of intelligentsia by the government have been investigated. Some of the main processes taking place within the modern Russian intelligentsia have been identified. The concepts of “liberal intelligentsia” and “patriotic intelligentsia” have been covered. The results of the discussions around further development of this phenomenon in the early 21st century have been summarized. The disunity and crisis, difficulties of self-identification of Russian intelligentsia as a result of its development in the latest decades have been emphasized.